Reconstruction of Economic Ideology in the Minister of Finance's Speech in Digital Media: A Critical Discourse Analysis Study - Debi Akmalindo Putra; Nurhayati Nurhayati; M. Afif Sholahudin A (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study investigates the reconstruction of economic ideology in the Minister of Finance’s speech disseminated through digital media using Norman Fairclough’s Critical Discourse Analysis framework. Employing a descriptive qualitative method, this research analyzes a transcript of the Minister of Finance’s speech published on the Kompas TV YouTube channel. The analysis integrates Fairclough’s three dimensions: text, discourse practice, and social practice to examine how economic meaning and power relations are constructed linguistically and socially. The findings reveal that economic ideology is reconstructed through the strategic use of crisis metaphors, authoritative modality, intertextual references, and evaluative lexical choices. These linguistic features position the state as a rational and technocratic authority capable of controlling national economic conditions. At the level of discourse practice, digital media plays a crucial role in amplifying and disseminating economic discourse to a wider public audience, shaping interpretation and reception. At the level of social practice, the discourse reproduces a technocratic-paternalistic ideology and reinforces economic nationalism to legitimize state intervention. This study contributes to Critical Discourse Analysis by highlighting economic discourse as a key site for ideological production and state power construction in the digital era, particularly within the Indonesian context.